Pengembangan e-modul sistem starter pada mata pelajaran pemeliharaan kelistrikan sepeda motor: Pengembangan, e-modul, sistem starter, sepeda motor - setiawanawan323 Awan setiawan (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to produce and test the feasibility of an e-module motorcycle starter system for class XII students of Motorcycle Business Engineering at SMK Negeri 1 Jamblang. The type of research used is research and development. The stages of e-module development with the Four-D development model are the definition stage, the design stage, the develop stage, and the dissemination stage. This research involves material experts, media experts, and students as research subjects and research objects in the form of assessment and response to the feasibility of e-modules, data collection techniques using questionnaires with quantitative descriptive data analysis techniques. The results showed that the e-module through a feasibility test from a material expert obtained a feasibility level of 3.05 with a